1993
DOI: 10.1161/01.str.24.9.1352
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-induced platelet defects.

Abstract: Background and Purpose: Numerous studies have demonstrated an association between acute cardiac events, cerebrovascular accidents, and cocaine use. The underlying mechanisms leading to these complications have not been well defined. Using various in vitro model systems, it has been reported that cocaine, up to or greater than an order of magnitude of the lethal dose, causes either inhibitory or proaggregatory effects on platelet function.Methods: To address these reported discrepancies, we examined the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…Our results confirmed and extended previous observations that chronic cocaine use is associated with platelet activation which is a prominent finding after recent consumption. Two reports showed cocaine-associated inhibition of platelet function assessed by light transmission platelet aggregation studies [18,19]. The apparent discrepancy with our findings may be explained by partial platelet activation in vivo which may cause a decrease in platelet response in vitro.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results confirmed and extended previous observations that chronic cocaine use is associated with platelet activation which is a prominent finding after recent consumption. Two reports showed cocaine-associated inhibition of platelet function assessed by light transmission platelet aggregation studies [18,19]. The apparent discrepancy with our findings may be explained by partial platelet activation in vivo which may cause a decrease in platelet response in vitro.…”
Section: Discussioncontrasting
confidence: 99%
“…In chronic users Rinder et al found increased expression of surface p-selectin on circulating platelets [17]. However, some studies have shown that cocaine may decrease platelet function under certain conditions [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…49 We found no direct evidence of peripheral platelet destruction or immune phenomena in our patient's peripheral blood smear or laboratory testing. Systemically, cocaine is shown to augment platelet aggregation 50,51 ; however, high-local concentrations may inhibit clot formation and lead to bleeding. 51 Neither, however, would explain the thrombocytopenia.…”
Section: Cocaine's Effect On Other Organsmentioning
confidence: 99%
“…Systemically, cocaine is shown to augment platelet aggregation 50,51 ; however, high-local concentrations may inhibit clot formation and lead to bleeding. 51 Neither, however, would explain the thrombocytopenia. Our patient's prothrombin and partial thromboplastin times were increased, but his fibrinogen level dropped to only 180 mg/dL at its lowest.…”
Section: Cocaine's Effect On Other Organsmentioning
confidence: 99%
“…Jennings and colleagues postulated that cocaine may inhibit platelet function, particularly when high local concentrations are achieved. 12 Thus studies directly exposing isolated platelets to cocaine in vitro, 12 28 or challenging isolated platelets in vitro after previous in vivo drug exposure, 29 are best suited to explain such local haemorrhagic events.…”
Section: Haemorrhagic Versus Thrombotic Effectsmentioning
confidence: 99%